Enhancing the cycle stability of milled Mg-Ni alloys: The role of Pd substitution on reversible electrochemical hydrogenation/dehydrogenation reactions - Jianling Huang; Jiabao Li; Yang Cai; Shiqian Zhao (Electrochemistry Communications)
The practical application of Mg-based alloys as anode materials for nickel-metal hydride (Ni-MH) batteries is hindered by serious capacity decay. To enhance their cycle stability and elucidate the underlying mechanism, this study investigates the influence of partially substituting Ni with Pd on the structural and electrochemical properties of milled Mg55Ni45 alloy, as well as their microstructural evolution during cycling. This work demonstrates the Pd addition enables reversible electrochemical hydrogenation/dehydrogenation reactions in the Mg2Ni phase and enhances the electrochemical reaction kinetics of the alloys. As a result, the addition of Pd improves both cyclic performance and rate capability of the milled alloy electrodes. The Mg55Ni45 alloy delivers a maximum discharge capacity of 488.65 mAh/g but decays to 110 mAh/g after only 13 cycles at a discharge current density of 50 mA/g. In contrast, the Mg55Pd4Ni41 alloy demonstrates a discharge capacity of 564.6 mAh/g and retains 277 mAh/g after 50 cycles. Notably, when subjected to a higher discharge current density of 300 mA/g, the Mg55Pd4Ni41 alloy displays an enhanced discharge capacity (401.49 mAh/g) compared to that of the Mg55Ni45 alloy (77.72 mAh/g).